Penerapan Balanced Scorecard Dalam Meningkatkan Kinerja Keuangan Perusahaan - Muhammad Rajali; Maya Macia Sari; Fanny Indah Lestari; Indah Permata Sari Sitorus Pane; Rafidha Yasmin Tarigan (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
The purpose of this writing is to discuss the application of the Balanced Scorecard (BSC) in companies to improve financial performance. The focus is on the concept and use of BSC as a strategic management tool without emphasis on specific research. The implementation of BSC is described as a holistic approach that allows companies to measure and manage their performance through four main perspectives: financial, customer, internal processes, and learning and growth. In discussing the application of the BSC, this paper highlights how this framework helps companies to reconcile strategic objectives with operational actions. An in-depth understanding of each BSC perspective is provided, with a particular focus on how non-financial aspects can support improved long-term financial performance. Cases of BSC use in companies as illustrative case studies are also included to provide a practical overview. The results show that the implementation of BSC can guide companies in achieving strategic balance, enabling management to make more informed and comprehensive decisions. The practical and strategic implications of implementing BSC without specific research are outlined as a potential guide for companies seeking to improve their financial performance through a balanced and integrated approach.